2022
DOI: 10.2196/36770
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Response Relationship of a Blended In-Person and Online Family-Based Childhood Obesity Management Program: Secondary Analysis of a Behavior Intervention

Abstract: Background The Early Intervention Program (EIP) was a 10-week, blended, in-person and online lifestyle intervention for families with children who were off the healthy weight trajectory. The engagement pattern and the dose response of EIP have not been examined. Objective The aims of this paper are to examine families’ engagement patterns with the EIP and to evaluate the dose-response relationship between EIP engagement patterns and physical activity an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The virtual delivery format has the potential to improve the flexibility and scalability of family-based lifestyle programs designed for children who are overweight or obese. The results from this study add to the existing body of literature showing the effectiveness of virtual and online health interventions [31,[34][35][36]. The family feedback received (eg, reminder sessions, portal tutorials, and maintenance programs) can help inform future virtual intervention designs.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The virtual delivery format has the potential to improve the flexibility and scalability of family-based lifestyle programs designed for children who are overweight or obese. The results from this study add to the existing body of literature showing the effectiveness of virtual and online health interventions [31,[34][35][36]. The family feedback received (eg, reminder sessions, portal tutorials, and maintenance programs) can help inform future virtual intervention designs.…”
Section: Discussionmentioning
confidence: 69%
“…In our previous study evaluating the dose-response relationship of the blended GH program, we showed that the online GH portal complemented the in-person GH sessions. Specifically, additional engagements with the portal were associated with greater improvements in child physical activity and parental support behaviors, habits, and identity for physical activity [34]. Future research is warranted to explore the dose-response relationship for the virtual GH program.…”
Section: Discussionmentioning
confidence: 98%
“…The 10-week hypertension management program was selected for adaptation for its proven success in improving PA levels (ie, daily steps) and blood pressure [30]. Furthermore, the research team evaluated the past success of the M-PAC framework in various web-based interventions that promote PA [31][32][33] and deemed this framework appropriate to guide an 8-week mHealth app.…”
Section: Steps 1 and 2: Empathize With Target Users And Specify Targe...mentioning
confidence: 99%
“…The second step of the integrate stage is to specify the target behavior to be used in the intervention. To do this, the research team reviewed the current public health guidelines [3,34] and conducted a literature search of empirical evidence to determine the optimal method for delivering an M-PAC PA intervention through a smartphone [31][32][33].…”
Section: Steps 1 and 2: Empathize With Target Users And Specify Targe...mentioning
confidence: 99%
“…Importantly, continuance of PA requires the development of reflexive processes of action control via habit and identity formation. While the overall evidence for the M-PAC framework is accumulating across populations for PA promotion including cancer populations ( Liu et al, 2022a ; Trinh et al, 2021 ; Perdew et al, 2021 ; Vallerand et al, 2018 ), to our knowledge, no application (app) intervention has been developed based on this framework.…”
Section: Introductionmentioning
confidence: 99%